2021
DOI: 10.3390/ijms22020609
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into Ankyrin Repeat-Containing Proteins and Their Influence in Ubiquitylation

Abstract: Ankyrin repeat (AR) domains are considered the most abundant repeat motif found in eukaryotic proteins. AR domains are predominantly known to mediate specific protein–protein interactions (PPIs) without necessarily recognizing specific primary sequences, nor requiring strict conformity within its own primary sequence. This promiscuity allows for one AR domain to recognize and bind to a variety of intracellular substrates, suggesting that AR-containing proteins may be involved in a wide array of functions. Many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 84 publications
1
16
0
Order By: Relevance
“…Previous reports have suggested that ankyrin repeat-containing proteins undergo a two-state folding transition, where they show a double sigmoidal-type thermal denaturation curve using CD. To see if this phenomenon holds true for gankyrin, we performed CD thermal denaturation experiments to characterize the structural stability of gankyrin in the presence and absence of our compounds. As shown in Figure B, we observed that gankyrin does in fact display a two-state folding transition similar to other ankyrin repeat-containing proteins.…”
Section: Results and Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Previous reports have suggested that ankyrin repeat-containing proteins undergo a two-state folding transition, where they show a double sigmoidal-type thermal denaturation curve using CD. To see if this phenomenon holds true for gankyrin, we performed CD thermal denaturation experiments to characterize the structural stability of gankyrin in the presence and absence of our compounds. As shown in Figure B, we observed that gankyrin does in fact display a two-state folding transition similar to other ankyrin repeat-containing proteins.…”
Section: Results and Discussionmentioning
confidence: 84%
“…We postulate that some of the α-helical content in gankyrin is still maintained due to increased interactions of critical residues found within gankyrin. This includes the canonical GxTPLHAA motif found in naturally occurring ankyrin repeats that require specific H-bonding and hydrophobic interactions to maintain its characteristic 90° L-shape solenoid fold . The presence of these compounds may be altering the packing and/or proximity of these important residues within gankyrin, limiting its capability to maintain its native fold.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AR domains were first discovered as a repeating sequence in Saccharomyces cerevisiae cell cycle regulator Swi6 and cell division control protein 10 (Cdc10) and Notch in Drosophila melanogaster [10]. AR domains act as scaffolds to facilitate protein-protein interactions in the cell [11,12] and are present in many eukaryotic proteins, making this domain potentially the most abundant repeat domain in the eukaryotic proteome [13]. FN3 is a very common constituent of animal proteins [14] and has been proven to be an established scaffold for developing nonantibody binding domains [15], which change the conformation of FN3 and eventually translate into structural changes across the membrane [12].…”
Section: Introductionmentioning
confidence: 99%
“…The 30- to 33-residue ankyrin repeat (AR) is one of the most common protein-protein interaction motifs in nature and a ubiquitous structural motif across the tree of life ( 24 , 25 ). Analysis of more than 1,900 bacterial species revealed that obligate intracellular bacteria have the highest percentage of AR-containing proteins (Anks) within their proteomes, reflective of their prominence as interfaces with eukaryotic processes ( 24 ).…”
Section: Introductionmentioning
confidence: 99%